The role of competitive intelligence and reverse engineering to achieve competitive advantage - سرور, منال جبار; محمد, حسام احمد (Journal of Economics and Administrative Sciences, 2013)
AbstractIn light of the great technological development and the emergence of globalization has increased global competition, where it became competitive exercise pressure on all sectors. In light of this companies mast enviorment depend on the means that keeps them on the competitive position through access to information about competitors in order to help them to draw a strategy that will achieve a competitive edge either through excellence or reduce the costs of their products and this means intelligence competitive and reverse engineering that help to gain information on competitors analyze and put of the decision-maker From this point formed the idea of ​​research in the statement of the role of competitive intelligence and reverse engineering to achieve competitive advantage, so the problem of research in several questions:* What is competitive intelligence and how it affects the competitive advantage?* How to help reverse engineering a competitive intelligence to achieve competitive advantage?So the search is aimed to the statement of cognitive underpinnings of intelligence and competitive reverse-engineering and its role in achieving competitive advantage through the company's strategy to achieve a lower cost or excellence. In order to achieve the objective of this research and put formulation of hypothesis basic message: help competitive intelligence, reverse engineering on achieved competitive advantage to achieve the goal of the research and test his hypothesis was divided into three Section Investigation singled out from the first and second display research methodology and theoretical framework, while the third on the last and most important conclusions and recommendations.